Understanding the influence of Remoteness on Culture and Socio-Economic of the Orang Asli in Malaysia - Ghani, Erlane K; Muhammad, Kamaruzzzaman; Hassan, Razinah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to understand the influence of remoteness on the culture and socio-economic of the indigenous people known as the Orang Asli in Malaysia. Specifically, this study focuses on the largest tribe of Orang Asli in Pahang known as the Jahut tribe. This study utilises semi-structured interviews to achieve the research objective. Three Orang Asli were selected as participants for the interview. The findings of this study record the remoteness, culture and socio-economic that shape the way of life of the Jahut tribe. This study finds that the culture and customs and unique taboos of the Jahut tribe are seen to be disappearing due to the currents of modernization and globalization. However, this study finds that the socio-economic situation of the Jahut tribe is still behind compared to most other Malaysians. There are also some unique customs and taboos that are still practiced among them. This findings show that such scenario are highly influence by the remoteness of location of the village which is quite far from the city. In addition, the inhabitants of a settlement are only inhabited by the same tribe of which in this study, Kampung Pian. This study can be used as an input for the government, academics and NGOs to plan their respective assistance and responsibilities activities.